The Safety of Building Structures Subject to Unusual Natural and Man-Made Disasters - Nguyen Van Pho (ASEAN Journal on Science and Technology for Development, 2006)
Previously, we often use the statistical data on natural disasters and mathematical tools such as probabilistic theory, mathematical statistics and random processes to express and analyze natural disasters' phenomena when dealing with the safety problem of building structures subject to natural disasters. However, due to unusual change of the global climate, natural disasters have changed essentially the intensity, frequency and the appearing time so we cannot rely on  the statistical data on natural disasters in the past to do that. Therefore, renovation of the thought on selection of plans, calculation, design, and evaluation of safety of building structures to accommodate to natural disasters and man-made disasters is a required task. This paper presents  some points of view of the authors, including: (i) Why should we renovate our thought on selection of plans, calculation, design, and evaluation of safety of existing structures? (ii) What are the old thought and the new thought on the safety of building structures? (iii) How to renovate the selection of building plan, calculation, design and evaluation of the safety of building structures? and (iv) How were some building structures in Vietnam decided according to the new thought?Some specific examples on the selection of building plan given in this paper are to illustrate the authors' opinions.